1980
DOI: 10.1017/s0021859600027957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein quality of poultry feedingstuffs. 2. Fish meal

Abstract: SummaryThe present study was made to evaluate the protein quality of 11 samples of fish meal (FM) covering a wide range of nutrient content to find a suitable laboratory method for predicting nutritive quality. The nutrient content of the samples ranged from 34 to 62% in crude protein, 28 to 48% in true protein and 0·99 to 2·87% in available lysine. The true protein content of FM was further partitioned into myogen, myosin and stroma proteins. The stroma protein accounted for 61% of total crude protein suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The defatted ground sample (0-5 g) was suspended in 75 ml of 0-1 N-HCl-sodium citrate (0-1 M) buffer containing 0-05 g pepsin and digested 0021-8596/80/2828-3030 $01.00 © 1980 Cambridge University Press as described in the previous study for the determination of in vitro pepsin-trypsin digestibility coefficients (Zombade, Lodhi & Ichhponani, 19806).…”
Section: In Vitro Protein Digestibilitymentioning
confidence: 99%
“…The defatted ground sample (0-5 g) was suspended in 75 ml of 0-1 N-HCl-sodium citrate (0-1 M) buffer containing 0-05 g pepsin and digested 0021-8596/80/2828-3030 $01.00 © 1980 Cambridge University Press as described in the previous study for the determination of in vitro pepsin-trypsin digestibility coefficients (Zombade, Lodhi & Ichhponani, 19806).…”
Section: In Vitro Protein Digestibilitymentioning
confidence: 99%
“…Taking this further, Matheson (1968a) (Matheson 1968b). Feeding trials with chicks and rats showed that lysine with a free e-amino group was not necessarily absorbed or utilized (Amadi and Hewitt 1975 Booth (1911) (Zombade et al 1980a); however, halfofthe variation in GPV was not explained. For oilseed meals, the relationship between GPV and available lysine was not significant (Zombade et al 1980b Carpenter (1960) accurately predicted available lysine whereas the method of Roach et al (196'7) gave misleadingly high values (Walz and Ford 1972 Roach et al (1967) assay values or to either Roach et al (1961) or Carpenter (1960) For personal use only.…”
mentioning
confidence: 99%